The innovation of functional foods in Asia: IFFA 2018 - Orada Chumphukam (2019)
Functional foods (FF) are commonly consumed by Asians, and this trend has increased in recent years. Despite the reported health benefits of FF, it is necessary scrutiny and updates of the underpinning research are important. The first international conference on functional food innovation in Asia (IFFA 2018) took place on January 22nd- 24th, 2018, at the University of Phayao, Thailand. Domestic and international speakers, researchers, nutritionists, dieticians, research scholars and students shared their knowledge and experience in FF research. Key features were the potential beneficial roles of FF in health and disease, the current situation with FF in Asia and innovative trends. The IFFA 2018 involved 2 keynote speakers, 34 invited speakers and 10 sessions. About 250 people from across Asia participated. Key themes, discussions, innovative opportunities, and future directions to link research in academia with health-directed applications as FF are summarised.